STRATEGI PENGEMBANGAN AGROINDUSTRI GULA SEMUT AREN - Nur Afni Evalia (Jurnal Manajemen & Agribisnis, 2015)
Aren is a type of palm that has a highly potential economic value. Lareh Sago Sub-district is the largest producer in the District of Lima Puluh Kota; however, it is only processed to produce wine and molded sugar. This study aimed to formulate a strategy for the sugar palm sugar agro-industrial development in Lareh Sagohalaban. The research method was a case study in the form of quantitative descriptive, and the data were processed using IFE/EFE, SWOT and AHP. The values obtained from IFE and EFE matrixes were 2.646 and 2.298 respectively. From the SWOT analysis, alternative strategies were obtained, namely, SO Strategy: Strengthening the R & D to develop market-based sugar processing for commercial scale and diversification of palm downstream products; WO Strategy: Improving upstream subsystem to develop nursery based on palm local seed varieties and providing institutional assistance; ST Strategy: Determining agro-technopark for palm industrialization, providing assistance in the form of appropriate packaging technology accordance with the standards, and WT Strategy: increasing commitment and cooperation among stakeholders in strengthening palm agro-industry, increasing marketing and promotion for the expansion and sanction policy for any company selling Aren in the form of wine. From the result of AHP analysis, the determinant factors in developing the business include Technology (0.439), the Government as the actor (0.577), and product diversification as the strategy (0.388).Keyword: Aren (palm), cluster- agro technopark, IFE/EFE matrixes, SWOT analysis, AHPABSTRAKAren (Arenga pinnata Merr) adalah jenis palma yang memiliki potensi nilai ekonomi yang tinggi. Kecamatan Lareh sago halaban merupakan penghasil Aren terbesar di Kabupaten Lima Puluh Kota, namun dalam pengolahannya masih mengolah menjadi gula cetak dan lebih banyak dalam bentuk tuak. Penelitian ini bertujuan merumuskan strategi pengembangan agroindustri gula semut aren di Kecamatan Lareh sago halaban. Metode penelitian adalah studi kasus dalam bentuk deskriptif kuantitatif. Teknik pengolahan data menggunakan analisis deskriptif, IFE/EFE,SWOT dan AHP. Nilai yang diperoleh dari matriks IFE (2,646 ) dan  EFE (2,298). Hasil alternative strategi menggunakan SWOT yaitu Strategi SO:Memperkuat litbang untuk riset pengolahan aren menjadi gula semut yang berkualitas, diversifikasi produk dan kemasan untuk komersialisasi gula semut aren.Strategi WO: Perbaikan sarana dan prasarana produksi gula semut untuk memenuhi standar ekspor dan pendampingan kelembagaan dari dinas-dinas terkait. Strategi ST: pemberian bantuan dana untuk peningkatan produksi gula semut aren, Penetapan kawasan agroteknopark untuk industrialisasi aren, pemberian bantuan berupa teknologi tepat guna dan teknologi packing. Strategi WT: peningkatan komitmen dan kerja sama antara semua stakeholder aren dalam penguatan agroindustri aren, Peningkatan promosi untuk perluasan pemasaran dan kebijakan dan sanksi yang menjual dalam bentuk tuak. Hasil Pengolahan AHP diperoleh faktor penentu adalah Teknologi (0,439) dengan pelakunya adalah Pemerintah (0,577) serta strategi yang diprioritaskan adalah Pemberian bantuan berupa teknologi tepat guna dan teknologi packing untuk skala komersil (0,258)Kata kunci: aren, agroteknopark, IFE-EFE, SWOT,  AHP